2018
DOI: 10.2118/184535-pa
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Optimization of Oilfield-Scale-Inhibitor Squeeze Treatments Delivered by Diving-Support Vessel

Abstract: Summary Oilfield-scale deposition is one of the important flow-assurance challenges facing the oil industry. There are a number of methods to mitigate oilfield scale, such as reducing sulfates in the injected brine, reducing water flow, removing damage by using dissolvers or physically by milling or reperforating, and inhibition, which is particularly recommended if a severe risk of sulfate-scale deposition is present. Inhibition consists of injecting a chemical that prevents the deposition of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Coupled with the elevated salinity, scaling threats can take place in subsurface, production tubing, subsea flowlines, and topsides facilities (Fan et al, 2012a). It has been reported that scale deposition is responsible for ∼20% of downtime for a major oil company across all regions (Vazquez et al, 2007). In shale play, water evaporation can be enormous due to hydraulic fracturing and pressure drawdown, resulting in a severe scaling threat (Vankeuren et al, 2017;Chang et al, 2019).…”
Section: Oilfield Flow Assurance and Mineral Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with the elevated salinity, scaling threats can take place in subsurface, production tubing, subsea flowlines, and topsides facilities (Fan et al, 2012a). It has been reported that scale deposition is responsible for ∼20% of downtime for a major oil company across all regions (Vazquez et al, 2007). In shale play, water evaporation can be enormous due to hydraulic fracturing and pressure drawdown, resulting in a severe scaling threat (Vankeuren et al, 2017;Chang et al, 2019).…”
Section: Oilfield Flow Assurance and Mineral Scalementioning
confidence: 99%
“…Although the aforementioned Ca-DTPMP SINMs can significantly improve inhibitor performance in terms of transportability in formation medium and squeeze lifetime, these materials might not be suitable for application in the field characterized by low water cut and/or high water sensitivity (Collins and Hewartson, 2002;Guan et al, 2006;Vazquez et al, 2007Vazquez et al, , 2016Chen et al, 2010). Since the aforementioned nanomaterials are water based, the water in the SINM package can damage the formation and impair well productivity due to mechanisms such as clay mobilization and pore constriction.…”
Section: Reverse Micelle Ca-dtpmp Nanofluidmentioning
confidence: 99%
“…The intelligent optimization method is optimizing fracturing parameters based on intelligent optimization algorithms, such as Genetic Algorithm (GA) [29] and Particle Swarm Optimization (PSO) [30]. Compared with the traditional optimization method, the intelligent optimization method can achieve the overall optimization of fracturing parameters and has better optimization accuracy.…”
Section: Introductionmentioning
confidence: 99%